Effectiveness of Storytelling Therapy on Creativity and Emotional Intelligence in Children with Separation Anxiety Disorder - Nazizadeh , Zahra; Ramadan, Parnian; Moradi , Sara; Seyyedbarghi , Azam sadat (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to evaluate the effectiveness of storytelling therapy on creativity and emotional intelligence in children with separation anxiety disorder.Methods and Materials: The present research is a quasi-experimental study with a pre-test, post-test design with a control group. The population of this study included all children aged 5 to 7 years old suffering from separation anxiety disorder, who attended clinical psychiatric centers in Tehran in the year 2023. The sample consisted of 30 subjects selected through convenience sampling and were randomly divided into two groups (15 in the experimental group and 15 in the control group), but the control group remained on a waiting list for treatment. Before and after ten treatment sessions, all participants were assessed with the Torrance Creativity Test (Torrance, 1979) and the Emotional Intelligence Scale (Mavroveli et al., 2008). Additionally, participants received a psychiatric diagnosis regarding the disorder in question. Data analysis obtained from the administration of questionnaires was performed using SPSS software in two parts: descriptive and inferential (covariance).Findings: The results of the covariance analysis showed that storytelling therapy improves creativity and emotional intelligence in children with separation anxiety disorder at the post-test stage.Conclusion: Therefore, it can be inferred from the findings that storytelling therapy can be effective in enhancing the creativity and emotional intelligence of children.